2017
DOI: 10.1073/pnas.1712706114
|View full text |Cite
|
Sign up to set email alerts
|

Electrical synapses mediate synergism between pheromone and food odors in Drosophila melanogaster

Abstract: In , the sex pheromone produced by males,-vaccenyl acetate (cVA), evokes a stereotypic gender-specific behavior in both males and females. As adults feed, mate, and oviposit on food, they perceive the pheromone as a blend against a background of food odors. Previous studies have reported that food odors enhance flies' behavioral response to cVA, specifically in virgin females. However, how and where the different olfactory inputs interact has so far remained unknown. In this study, we elucidated the neuronal m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 73 publications
(101 reference statements)
2
59
0
Order By: Relevance
“…The responses to the alcohols were observed in OSN type ab1A (Or42b) with a stronger affinity to ethanol, and in ab2A (Or59b) and pb1A (Or42a) with stronger responses towards methanol. We also noted a synergy between ethanol exposure and at1A response to cVA (which has been demonstrated previously 6,20,21 ), as well as a possible synergy between at4A responses towards methanol exposure and ML ( Supplementary Figure 5d,e), although neither alcohol directly activated these trichoid associated OSNs when presented alone. At the OSN level, we did not observe any variation in SSR response based on mating status (mated vs. non-mated males) (Figure 3d).…”
supporting
confidence: 84%
See 1 more Smart Citation
“…The responses to the alcohols were observed in OSN type ab1A (Or42b) with a stronger affinity to ethanol, and in ab2A (Or59b) and pb1A (Or42a) with stronger responses towards methanol. We also noted a synergy between ethanol exposure and at1A response to cVA (which has been demonstrated previously 6,20,21 ), as well as a possible synergy between at4A responses towards methanol exposure and ML ( Supplementary Figure 5d,e), although neither alcohol directly activated these trichoid associated OSNs when presented alone. At the OSN level, we did not observe any variation in SSR response based on mating status (mated vs. non-mated males) (Figure 3d).…”
supporting
confidence: 84%
“…This is similar to ecologically relevant concentrations of CO 2 , where two neural pathways are weighed against each other in order to control behavioral valence 7 . Crosstalk has also been shown to occur between information regarding different types of odorants 20,27,28 , and may play a larger role in physiological state-dependent coding, as well as in determining feeding and oviposition preferences across the Drosophila genus, for example, in divergent preferences for different stages of host fermentation [29][30][31] .…”
Section: Or42bmentioning
confidence: 99%
“…(2020) 10:5689 | https://doi.org/10.1038/s41598-020-62520-ywww.nature.com/scientificreports www.nature.com/scientificreports/ The perturbation of courtship behavior was observed in dUbqn-depleted flies. Drosophila has complex behaviors that are regulated by dopamine and serotonin such as feeding, locomotion, and courtship behaviors40,41,43,44 . From LC-MS/MS data, we also found reductions in dopamine and serotonin levels under…”
mentioning
confidence: 99%
“…The response to food and mate olfactory cues is strongly interconnected in Drosophila (Das et al 2017;Gorter et al 2016;Lebreton et al 2015) and DmelOr69a is also tuned to the newly identified female pheromone (Z)-4-undecenal (Z4-11Al), in addition to food odorants (Lebreton et al 2017). Curiously, Z4-11Al is also found in citrus essential oil (Chisholm et al 2003).…”
Section: Introductionmentioning
confidence: 99%